Robert Alexy, fundamental rigths, legal speach and practical rationality. ¿A realistic reading? - Pozzolo, Susanna (2017)
This article focuses on the analysis of the literature produced by Robert Alexy, a renowned German jurist, focusing on the concept of fundamental rights, which are, in a constitutional state of law, the ultimate goal of the legal system. Thus, for Alexy the rights of people are not moral, but rather legal. It is in this sense and taking as a starting point the conception of fundamental rights that the author proposes a tentative reading from a moderate realistic perspective of some aspects of the theoretical position of Alexy.